ADAPTIVITY EVALUATION OF PEA VARIETIES SUITABLE F OR FREEZING IN THE SOUTHWEST-ERN OF CENTRAL CHERNOZEM ZONE - A. S. Shulpekov; S. M. Sirota; E. G. Dobrutskaya; E. P. Pronina (Овощи России, 2015)
The characteristics of adaptability of 24 pea varieties to justify the use of the assortment in the technology of conveyor cultivation of raw green peas for freezing in conditions of the south-west of the CCZ is presented.